Faktor yang mempengaruhi Harga Saham pada Perusahaan Sektor Teknologi di Bursa Efek Indonesia - Nurlaily, Liafatra; Mela, Fefti Yulian; Agustina, Fitria Fertha (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2023)
The purpose of this study is to examine the effect of total assets, cashflow in operating activities, cashflow in investing activities, cashflow in financing activities, and ROE on the stock prices of technology sector companies listed on the Indonesia Stock Exchange in 2022-2023. This research is a quantitative study using secondary data and data collection techniques in the form of purposive sampling. There are 33 companies that make up the population, but only 22 can be sampled and are eligible to be the object of this study. Hypothesis testing was carried out using multiple regression analysis using SPSS 25 software. The results showed that there was a positive and significant effect of total assests on stock prices, there was no significant effect of cashflow in operating activities, cashflow in investment activities, cashflow in financing activities, and ROE on stock prices.